An exploration of the growth in mathematical understanding of grade 10 learners - Mokwebu, Disego Jerida (University of Limpopo, Turfloop Campus, 2013)
In this study, I presented the exploration of Mpho’s growth in mathematical understanding. Mpho is a grade 10 mathematics learner. To fulfil such, a qualitative research method was employed. I explored her growth in understandings in the context of co-ordinate geometry, exponents, and functions. Data generation, management and representation were guided by the notion of teaching experiments. Analysis was done through mapping learner’s growth of mathematical understanding using Pirie-Kieren’s (1994) model. Findings suggest that learner’s growth in mathematical understanding can be observed, mapped and improved with the aid of probing questions.
Thesis (M.Ed. (Mathematics Education)) -- UNiversity of Limpopo, 2013
Keywords: Mathematics teaching; Mathematical understanding; Mathematics -- Study and teaching (Secondary) -- South africa -- Limpopo; Education, Secondary -- South Africa -- Limpopo